Tri- and di-fluoroethylation of alkenes by visible light photoredox catalysis. Issue 9 (13th March 2018) - Pan, Xiao-Yang; Zhao, Yue; Qu, Hong-An; Lin, Jin-Hong; Hang, Xiao-Chun; Xiao, Ji-Chang
Abstract : The photoredox-catalyzed solvent-dependent tri-/di-fluoroethylation of alkenes with sulfonium salts (Ph2 S + CH2 RF TfO − ) (RF = CF3 or HCF2 ) is described. Abstract : The tri- and di-fluoroethylation of alkenes with sulfonium salts, (Ph2 S + CH2 RF TfO − ) (RF = CF3 or HCF2 ), by visible light photoredox catalysis to give tri-/di-fluoroethyl alkenes or methoxytri-/di-fluoroethylation products are described. It was found that varying the reaction solvent led to changes in the reaction path.